State of the art of bacterial chemotaxis - Karmakar, Richa (Journal of basic microbiology, 2021)
Bacterial chemotaxis is a biased movement of bacteria toward the beneficial chemical gradient or away from a toxic chemical gradient. This movement is achieved by sensing a chemical gradient by chemoreceptors. In most of the chemotaxis studies, Escherichia coli has been used as a model organism. E. coli have about 4–6 flagella on their surfaces, and the motility is achieved by rotating the flagella. Each flagellum has reversible flagellar motors at its base, which rotate the flagella in counterclockwise and clockwise directions to achieve “run” and “tumble.” The chemotaxis of bacteria is regulated by a network of interacting proteins. The sensory signal is processed and transmitted to the flagellar motor by cytoplasmic proteins. Bacterial chemotaxis plays an important role in many biological processes such as biofilm formation, quorum sensing, bacterial pathogenesis, and host infection. Bacterial chemotaxis can be applied for bioremediation, horizontal gene transfer, drug delivery, or maybe some other industry in near future. This review contains an overview of bacterial chemotaxis, recent findings of the physiological importance of bacterial chemotaxis in other biological processes, and the application of bacterial chemotaxis.